The Art of relic Cults in Trecento Venice: Corpi sancti as a Pictorial Motif and Artistic Motivation - Munk, Ana (Array, 2006)
This text focuses on scenes showing pilgrims venerating the tomb of a saint in Venetian and mid- and late-Trecento paintings which can be securely related to specific relic sites in Venice. The Pala feriale, the Saint Lucy altarpiece, the altarpiece fragment with stories from the life of the Blessed Giuliana Collalto, and the painted panel from the tomb of Leone Bembo are examples of paintings by Paolo Veneziano and like-minded artists from his circle who reconceived pictorial hagiographies to include interactions of pilgrims with corpi sancti. Although only Pala feriale can be securely dated to mid-Trecento and Andrea Dandolo's dogeship, Dandolo's keen interest in relic orchestration has contributed to a stronger pictorial formulation of "the bodies of saints which are whole and uncorrupted" (as an eraly Trecento pilgrim put it).